2012
DOI: 10.1002/jbmr.1674
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is associated with impaired bone mass development in young adult men: A 5-year longitudinal study

Abstract: It has previously been shown that smoking is associated with reduced bone mass and increased fracture risk, but no longitudinal studies have been published investigating altered smoking behavior at the time of bone mass acquisition. The aim of this study was to investigate the development of bone density and geometry according to alterations in smoking behavior in a 5-year, longitudinal, population-based study of 833 young men, age 18 to 20 years (baseline). Furthermore, we aimed to examine the cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
3
19
0
1
Order By: Relevance
“…Longitudinal studies of adolescent boys and girls in early adulthood have shown adverse effect of smoking [21,43]. In our study, smoking was negatively associated with BMD at the hip only in boys.…”
Section: Discussionsupporting
confidence: 38%
“…Longitudinal studies of adolescent boys and girls in early adulthood have shown adverse effect of smoking [21,43]. In our study, smoking was negatively associated with BMD at the hip only in boys.…”
Section: Discussionsupporting
confidence: 38%
“…In fact, several studies have demonstrated the protective effects of physical activity over the life course on adult bone health [78], and the especially important role of physical activity in the growing years [79] and of competitive sports in early life in Swedish men [80]. There is similarly increasing evidence of the deleterious effects of smoking on bone health in general [81], and especially that of smoking in the teenage and young adult years on peak bone mass in European men [82,83]. Not all of the childhood SES association with adult bone strength in the femoral neck was explained by health behaviors in this study, suggesting that other mechanisms such as food choices and nutrition adequacy may also play a mechanistic role.…”
Section: Discussionmentioning
confidence: 99%
“…A five year longitudinal study investigated the development of bone density in a population of 833 young men (18-20 years), using high resolution peripheral Quantitative Computed Tomography. Men who had started smoking had considerably smaller increases in total body and lumbar spine BMC, and substantially greater decreases at the total hip and femoral neck, than men who were non smokers at both baseline and follow-up visits 5 . Epidemiological surveys on post-menopausal women show that smokers loose significantly more cortical bone than non smoking counterparts 6 .…”
Section: Epidemiologymentioning
confidence: 99%